2020
DOI: 10.1364/ao.402011
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of supersonic jet screech with focused laser differential interferometry

Abstract: Focused laser differential interferometry (FLDI) is used to measure a well-characterized, 17 kHz screech tone emitted from an underexpanded Mach 1.5 jet. Measurements are made at numerous spatial locations in and around the jet flow-field, where intrusive diagnostics would otherwise influence the flow-field. Results from FLDI measurements are shown to agree with measurements from microphones and analyses of high-speed schlieren. The agreement is used to demonstrate FLDI is a valid and accurate technique for me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This is done to ensure that measured results are accurate and/or to provide measurements of mixed resolution or response (e.g. with schlieren and pressure probes [1], particle image velocimetry (PIV) and molecular tagging velocimetry [2], schlieren and PIV [3], pressure-sensitive paint and pressure probes [4], Mach-Zehnder interferometry and focused laser differential interferometry (FLDI) [5], FLDI and high-speed schlieren (HSS) [6,7], etc). Often, the application of different methods does not occur at the same exact spatial location and may not be simultaneous due to instrument or test facility constraints (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is done to ensure that measured results are accurate and/or to provide measurements of mixed resolution or response (e.g. with schlieren and pressure probes [1], particle image velocimetry (PIV) and molecular tagging velocimetry [2], schlieren and PIV [3], pressure-sensitive paint and pressure probes [4], Mach-Zehnder interferometry and focused laser differential interferometry (FLDI) [5], FLDI and high-speed schlieren (HSS) [6,7], etc). Often, the application of different methods does not occur at the same exact spatial location and may not be simultaneous due to instrument or test facility constraints (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In these works, the lines-of-sight of the FLDI and HSS instruments were orthogonal to one another, which may not be practical or possible when measurements are performed in wind tunnel facilities with limited optical access. Examples of the non-simultaneous application of schlieren and FLDI techniques to study flow phenomena can be found in [6,7,[13][14][15]. Additionally, facility operators may require schlieren visualization as a means of monitoring flow quality, which may otherwise be obscured by the presence of another instrument.…”
Section: Introductionmentioning
confidence: 99%